2022
DOI: 10.1186/s13053-022-00239-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward preimplantation genetic testing and quality of life among individuals with hereditary diffuse gastric cancer syndrome

Abstract: Background Hereditary Diffuse Gastric Cancer (HDGC) syndrome is an autosomal dominant hereditary cancer predisposition associated with germline pathogenic/likely pathogenic variants in the CDH1 gene. Identifying early stage HDGC is difficult, and prophylactic measures can be effective in preventing incidence. Preimplantation Genetic Testing (PGT) can provide information about CDH1 variant status, HDGC risk, and limit familial transmission of CDH1 variants. To date, however, little is known abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In Shah al. 's study targeting patients with CDH1 variants, 40% of respondents stated they wou consider PGT, 35% would not and 25% were uncertain; 90.5% of patients thought th physicians should discuss PGT with individuals carrying CDH1 variants [47].…”
Section: Patients' Opinionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Shah al. 's study targeting patients with CDH1 variants, 40% of respondents stated they wou consider PGT, 35% would not and 25% were uncertain; 90.5% of patients thought th physicians should discuss PGT with individuals carrying CDH1 variants [47].…”
Section: Patients' Opinionmentioning
confidence: 99%
“…In Shah et al's study, of the two CHD1 carriers who wanted to have a biological child, one was "very likely" to use PGT, whereas the other one was "very unlikely". Among respondents who already had children, a small majority indicated that they would have considered using PGT if it had been available [47].…”
Section: Reproductive Factorsmentioning
confidence: 99%
See 2 more Smart Citations